From north to south: Mapping circus training in Brazil (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
Over the past 40 years, we have observed the process of developing numerous training spaces in circuses. The main objective of this study is surveying these spaces in Brazil. To this end, an exhaustive search was carried out via internet, followed by the application of an online questionnaire, ending with a thorough validation process. The results show that, in fact, there has been a great growth in the sector, especially in the last ten years, with a significant discrepancy in the distribution of training spaces across the different regions of the country. We have noted, moreover, the predominance of free and short courses, with little offer of professional courses, which require greater infrastructure, budget and number of professionals.
Keywords: Training places; Professional education; Circus school